Convergence Domains of AOR Type Iterative Matrices for Solving Non-Hermitian Linear Systems (Journal of Computational Mathematics, 2021)
We discuss AOR type iterative methods for solving non-Hermitian linear systems based on Hermitian splitting and skew-Hermitian splitting. Convergence domains of iterative matrices are given and optimal parameters are investigated for skew-Hermitian splitting. Numerical examples are presented to compare the effectiveness of the iterative methods in different points in the domain. In addition, a model problem of three-dimensional convection-diffusion equation is used to illustrate the application of our results.
Keywords: Convergence; AOR type iterative methods; Skew-Hermitian splitting; Hermitian splitting; Linear systems.